Photovoltaic Thermal (PVT) System with and Without Fins Collector: Theoretical Approach - Muhammad Zohri; Nurato Nurato; Ahmad Fudholi (Institute of Advanced Engineering and Science, 2017)
The fins collector design for solar thermal has widely been used and it has a higher thermal efficiency than without Fins. Photovoltaic thermal (PV/T) system produced Electrical and thermal energy instantaneously. Mathematical modeling based on steady-state thermal analysis of PV/T system with and without fins was conducted with matrix inversion method. The value results show that the PV/T system with fins collector is higher thermal and electrical efficiency than without fins.